Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Berpikir Kreatif Pada Siswa Kelas XI di SMA Negeri 6 Sigi - Hiska, Hiska; Jamhari, Mohammad; Windarsih, Yulia; Rafiqa, Rafiqa; Bialangi, Mursito S.; Ramadhan, Achmad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the effect of the Discovery learning model on students' creative thinking skills in biology education at the senior high school level. This study used an experimental design, involving pre-test and post-test to observe changes in students' creative thinking skills after implementing the Discovery learning approach. Data were collected through tests, observations, and student questionnaires, then analyzed using statistical methods to determine the effectiveness of the model. The results showed that (1) there was a significant improvement in students' creative thinking skills, as indicated by increased scores in both cognitive and affective domains; (2) students showed higher motivation and active participation during the lesson; (3) Discovery learning is effective in improving creative thinking skills among biology students; (4) integrating the Discovery learning model into biology teaching can contribute positively to students' learning processes and outcomes, encouraging a more active and student-centered approach. Thus, the importance of innovative teaching methods that foster creative thinking in science education.